MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA KELAS X AGRIBISNIS TANAMAN PANGAN DAN HORTIKULTURA SMKN 2 BATU MENGGUNAKAN TEKNIK ROLE PLAY - Erlis Kurniawati (Melati Institute, 2023)
In an increasingly connected world, English language skills are of key importance for students in vocational high schools who want to succeed in the future. Teachers need to be more creative in English teaching and utilize environmental media to increase students' interest. The use of Role Play technique in English learning outside the classroom, aims to avoid students' boredom and motivate them, while utilizing real objects such as plants, fruits, and agricultural tools. Students are also given the freedom to use apps and social media to upload videos of English conversations resulting from role play activities. The conclusion of this description is that the role play technique in learning English is very effective and attracts students' interest in learning; the systematic and careful preparation of the module is not only HOTS-oriented, but also integrates 21st century literacy and skills, preparing for the golden generation of 2045; and students gain an interesting and fun learning experience.